Plasma-assisted priming : improved germination and seedling performance of papaya - Deng-Ke, Xi; Ling Yap, Seong; Nitturi Naresh Kumar,; Chian, Cheng Toh; Ishikawa, Kenji; Hori, Masaru (Penerbit Universiti Kebangsaan Malaysia, 2023)
Papaya is a one of the important tropical fruit crops with a global export of 353 ktonnne reported in 2020. The germination of papaya seed is erratic and often non-uniform. Plasma assisted priming of seed was performed at atmospheric pressure in a parallel plate dielectric barrier discharge system. The germination rate of papaya seeds and the growth performance of the seedling were monitored for several treatment plans combining the atmospheric pressure plasma treatment with soaking of seed in deionized water. An enhanced germination rate of 92% was obtained by the plasma assisted priming, compared to the untreated of 60%. The plasma assisted priming performed by plasma treatment and soaking in an opposite sequence showed different requirement and possibly involved different mechanisms. The treatment time was reduced to only 4 minutes for pre-soaked seeds, otherwise the germination rate increased with the plasma treatment time from 3 to 30 min treatment. The plasma assisted priming approaches were also found enhancing seedling growth performance. The treated seedling grows about two times bigger and the dried mass measured after 30 days was more than 100% compared to that of the untreated and hot water treated seeds.